Duodenal eosinophils as predictors of symptoms in coeliac disease: a comparison of coeliac disease and non-coeliac dyspeptic patients with controls. (2nd July 2020) - Potter, Michael D.; Hunt, James S.; Walker, Marjorie M.; Jones, Mike; Liu, Cheng; Weltman, Martin; Talley, Nicholas J.
Abstract: Introduction: Duodenal eosinophilia is a key feature of functional dyspepsia, particularly in those with early satiety. Duodenal eosinophilia is also recognised in coeliac disease, although its relevance to symptoms is not understood. We aimed to determine if duodenal eosinophilia is present in patients with coeliac disease presenting with dyspepsia, and whether other histological characteristics were associated with clinical features on presentation. Methods: The coeliac study population comprised 61 patients with a new presentation of coeliac disease to a single centre from 2003 to 2013. A standard symptom assessment was documented for all patients. The control population (55 adults) presenting for endoscopy without coeliac disease was drawn from the same centre with similar demographics for age and gender. Duodenal biopsies from both groups were assessed for eosinophil counts and histological features. Results: Dyspepsia was present in 18.0% of coeliac patients and early satiety in 24.6%. The eosinophil counts were significantly higher in the stomach (12.1/mm 2 vs. 4.0/mm 2, p  < .001) and duodenum (60.4/mm 2 vs. 18.0/mm 2, p  < .001) of coeliac patients compared with controls. There was no significant difference in the mean duodenal eosinophil count in coeliac disease with and without early satiety (55.4/mm 2 vs. 66.9/mm 2, p  = .51). Duodenal eosinophilia was not associated with the severity of coeliac enteropathy. The degree of villous atrophy was associated with iron deficiency at presentation ( p  = .01), but not symptoms. Conclusions: Although duodenal eosinophil counts are higher in coeliac disease than controls, we were not able to demonstrate an association with presenting symptoms or markers of disease severity.